A Survey of Added Vitamins and Trace Minerals in Diets Utilized in the U.S. Swine Industry - Jamil E. G. Faccin; Mike D. Tokach; Jason C. Woodworth; Joel M. DeRouchey; Jordan T. Gebhardt; Robert D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2022)
From November 2021 to February 2022, 37 swine nutritionists representing 29 production systems and 8 nutrition supplier companies in the United States were surveyed about added vitamins and trace mineral concentrations in swine diets. Respondents were asked to provide vitamin and trace mineral inclusion rates, weight ranges associated with each dietary phase, and number of sows utilizing their nutritional recommendations. Survey participants represented 4.38 million sows, or 72% of the U.S. industry. Data were compiled into 3 nursery phases (weaning to 15 lb; 15 to 25 lb; and 25 to 50 lb), 3 finishing phases (50 to 120; 120 to 220; and 220 lb to market), gilt development, gestation, lactation, and boar diets. Within each dietary phase, the vitamins and trace minerals of interest included: vitamin A, vitamin D, vitamin E, vitamin K, thiamin, riboflavin, niacin, pantothenic acid, pyridoxine, biotin, folic acid, vitamin B12, choline, vitamin C, carnitine, copper, iodine, iron, manganese, selenium, zinc, cobalt, and chromium. Descriptive statistics used included: average, weighted average (determined by the total number of sows), median, minimum, maximum, 25th percentile (lowest quartile), and 75th percentile (highest quartile). In addition, all average vitamin and trace mineral concentrations within each phase of production were compared to the requirement estimates reported in the NRC. The results of this survey follow similar trends observed in a previous survey in 2016. Nutritionists generally supplemented vitamins and trace minerals well above the NRC (2012) requirements. However, greater variation among respondents was observed in all vitamins and trace minerals, particularly in the fat soluble vitamins. Also, the use of alternative sources of vitamin D (25-OH-D3), E (natural, d-alpha-tocopherol), and organic or chelated minerals like copper, manganese, selenium, and zinc is becoming more frequent. In addition, comparisons to the most recent NRC (2012) requirement estimates highlight the necessity of future research to better understand vitamin and trace mineral requirements in swine diets.
Keywords: diet formulation; nutrition; swine; trace minerals; vitamins